Uso del juego didáctico como herramienta para mediar los valores morales en niños y niñas de 5 años de la I.E inicial N°231 Sector Atahualpa - Pérez Armas, Mily (2010)
The present investigation consisted in developing a proposal once was based in the application of the learning game tool stop to mediata the moral values in the five - years boys and girls elderly, of the lnitial Educational lnstitution N° 231 of the Sector Atahualpa located in the district of Rioja. The investigation happened due to the interest to improve behavior that they show sorne boys and girls institutional Educational, most of all in the located around Rioja city; Under the circumstances, general objective consisted in proposing a viable alternativa that 1 improved significantly the practica of the solidarity's moral values, tolerance, self-esteem and responsibility, on the basis of the background and existent theories, than the proposal in the didactic games based will improve the said- moral values practica. In the operating part, it was worked up with a sign once was conformad for 18 children and 9 little girls, who were evaluated by means of a pretest to the initiating experiment and a postest to the finalizing . intention was of pointing out the differences among both tests it than finally, 1 would pay tribute to the hypothesis's contrastation. In like manner, investigation was conducted softly a design preexperimental, formulated the statistical hypothesis with the 95 trustworthy level. In arder to the contrastation of the hypothesis and according to the data's natura, 1 use test - Student arder to the differenca off, taking place accept fact-finding hypothesis, it as one implicates the learning game. has improved significantly the moral worths practica among the five- years boys and girls of her. Equally, it was evidencad the boys and girls that were presenting to the start practical to fairly negativa in moral worths, they got better significantly arrive to the levels of fairly positiva to plus sign as to the solidarity's practica, toleranca, self-esteem and responsibility. Equally, it was evidenced than the boys and girls that were presenting to the start practical refusal to fairly negativa in moral worths, they got better significantly to arrive to the levels of fairly positiva to plus sign as to the solidarity's practica, tolerance, self-esteem and responsibility.